2021
DOI: 10.1080/08820538.2021.1896752
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the morphological and biomechanical characteristics of keratoconus, forme fruste keratoconus, and normal corneas

Abstract: Purpose: To explore the feasibility of corneal morphological and biomechanical parameters for keratoconus and forme fruste keratoconus diagnosis. Methods: This case-control study included a total of 517 eyes from 408 keratoconus patients (KC group), 83 eyes from 83 forme fruste keratoconus patients (FFKC group), and 158 eyes from 158 patients with normal corneas (NL group). All subjects underwent routine ophthalmologic examinations. Pentacam and Corneal Visualization Scheimpflug Technology (Corvis ST) were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…speed of corneal apex at first applanation (A1V) and shorter first applanation time (A1T). Interestingly, the alteration of corneal biomechanical parameters in patients with symptoms and signs of DED except A2L were consistent with the alteration that was found in patients with keratoconus [21][22][23][24][25][26]. Theoretically, an earlier applanation, which is represented as a shorter time to the first applanation (A1T) and a higher velocity at the first applanation (A1V), suggests a softer cornea.…”
Section: Plos Onesupporting
confidence: 81%
See 1 more Smart Citation
“…speed of corneal apex at first applanation (A1V) and shorter first applanation time (A1T). Interestingly, the alteration of corneal biomechanical parameters in patients with symptoms and signs of DED except A2L were consistent with the alteration that was found in patients with keratoconus [21][22][23][24][25][26]. Theoretically, an earlier applanation, which is represented as a shorter time to the first applanation (A1T) and a higher velocity at the first applanation (A1V), suggests a softer cornea.…”
Section: Plos Onesupporting
confidence: 81%
“…Likewise, a higher velocity at the second applanation (A2V) suggested more compliant cornea. In clinical setting, various studies have compared corneal biomechanical parameters between normal and keratoconic eyes using Corvis ST. Five corneal biomechanical parameters including A1T, A2T, A1V, A2V, HC-radius and HC-DA consistently showed the alteration between normal and keratoconic eyes, while the other parameters demonstrated no significant difference [21][22][23][24][25][26]. Similar to keratoconic eyes, we found that the increase in severity of DED resulted in the alteration of corneal biomechanical parameters including HC-radius, A2V and A1T.…”
Section: Plos Onementioning
confidence: 50%
“…The Ocular Response Analyzer (ORA; Reichert, Buffalo, NY, United States) which provided great knowledge of the corneal biomechanics was one of the methods that were used in the clinic ( Luce, 2005 ) but it cannot exhibit the dynamic corneal response (DCR) parameters. In 2010, a visual display method that was based on corneal dynamic deformation video using an ultra-fast Scheimpflug camera combined with a classic non-contact tonometer was introduced ( Eliasy et al, 2018 ; Krysik et al, 2018 ; Guo et al, 2021 ). The non-contact tonometer is called corneal visualization Scheimpflug technology (Corvis ST; Oculus Optikgeräte GmbH, Wetzlar, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical changes often precede changes in corneal topography. Guo et al [11] concluded that cone corneas do not have morphological abnormalities at the beginning but generally have photomechanical abnormalities. In this study, to assess the ability of corneal biomechanics in the diagnosis of early cone corneas, some important parameters of Pentacam and Corvis ST were included simultaneously.…”
Section: Introductionmentioning
confidence: 99%